Dopagem e formação de heterojunções como estratégias para o melhoramento da propriedade fotocatalítica de Ag3PO4 - Trench, Aline Barrios (2022)
In recent years, the growing technological and industrial activities in sectors such as pharmaceuticals and textiles have shown side effects on the environment and human health. Such effects are related to the generation of harmful waste and its inappropriate disposal to the environment, mainly aquatic, directly impacting human and animal health. Among several processes for the treatment of these residues, heterogeneous photocatalysis has been considered an effective method for this purpose. With this, the search for new materials and the improvement of the properties of photocatalysts have grown abruptly. Due to its intrinsic photocatalytic activity for the degradation of organic compounds, silver phosphate (Ag3PO4) has been widely researched in order to improve its properties for the treatment of contaminated effluents. The formation of heterojunctions between semiconductors and also their doping have been shown to be efficient in improving the photocatalytic activity of Ag3PO4 for the degradation of dyes and drugs. Thus, this study had as main objective the modification of Ag3PO4 through doping with tungsten (W) and separately, through the formation of heterojunction with silver tungstate (α-Ag2WO4). In both works, the materials were synthesized by the chemical co-precipitation method and as main results, the doping of W in the Ag3PO4 structure caused the formation of disordered [AgO4], [PO4], and [WO4] clusters, which generate intermediate energy levels in the band gap region. These levels delay the electron-hole pair recombination process, resulting in an improvement in the photocatalytic performance of doped materials for the degradation of Rhodamine B dye, Cephalexin antibiotic, and Imidacloprid pesticide, under visible light irradiation. In addition, the presence of W in Ag3PO4 showed a 16-fold increase in bactericidal performance against methicillin-resistant Staphylococcus aureus bacteria. For the formation of heterojunction, it was observed that the material containing 24 wt% of α-Ag2WO4 showed superior photocatalytic activity for the degradation of Rhodamine B dye compared to the separated materials. Based on the reduction potentials of the valence and conduction bands of α-Ag2WO4 and Ag3PO4, obtained experimentally by the Mulliken electronegativity method, a type I heterojunction charge transfer mechanism was proposed for these materials. In addition, the formation of metallic silver nanoparticles at the semiconductors interface was observed, acting as a bridge and increasing the transfer and separation of charges between the semiconductors. Thus, in this study it was possible to obtain photocatalyst materials and improve the photocatalytic properties of Ag3PO4 through doping with W and the formation of heterojunction with α-Ag2WO4.